Glomerular Damage in Trichloroethylene-Sensitized Mice: Targeting Cathepsin L-Induced Hyperactive mTOR Signaling - Feng Wang; Feng Wang; Yuying Dai; Meng Huang; Chenchen Zhang; Liping Huang; Hui Wang; Hui Wang; Liangping Ye; Liangping Ye; Qifeng Wu; Xuejun Zhang; et al. (Frontiers Media S.A., 2021)
Trichloroethylene (TCE) is a serious health hazard for workers with daily exposure, causing occupational medicamentosa-like dermatitis due to TCE (OMDT) and glomerular damage. Recent studies suggest that mTORC1 signaling is activated in various glomerular disorders; however, the role of mTORC1 signaling in TCE-induced glomerular damage remains to be explored. In the present study, 6 OMDT patients were enrolled and a TCE-sensitized mouse model was established to investigate molecular mechanisms underlying the glomerular damage associated with OMDT. Glomerular damage was assessed by levels of urine nephrin, H&E staining, and renal function test. Ultrastructural change of podocyte was investigated by transmission electron microscopy. The podocyte-related molecules including nephrin, α-actinin-4, and integrin β1 were visualized by immunofluorescence. The activation of mTORC1 signaling was confirmed by Western blot. Glomerular apoptosis was examined by the TUNEL test and Western blotting. Expression and location of cathepsin L (CTSL) were assessed by RT-PCR and immunofluorescence. Our results showed that TCE sensitization caused damage to glomerular structural integrity and also increased the activation of mTORC1 signaling, which was accompanied by podocyte loss, hypertrophy, and glomerular apoptosis. Importantly, we also found that over-expressed CTSL was mainly located in podocyte and CTSL inhibition could partially block the activation of mTORC1 signaling. Thus, our findings suggested a novel mechanism whereby hyperactive mTOR signaling contributes to TCE sensitization-induced and immune-mediated glomerular damage via CTSL activation.